2022
DOI: 10.47577/tssj.v28i1.5760
|View full text |Cite
|
Sign up to set email alerts
|

The potential job opportunities for Halal Science Graduates in education sector in Negara Brunei Darussalam

Abstract: A concern for graduates in Brunei Darussalam is the difficulty of finding a stable career after graduation. Although Brunei is considered one of the richest countries in the world with a relatively small population, the unemployment rate keeps increasing, which is a problem for future graduates from various universities in this country. Therefore, this research focuses on studying the potential employment opportunities for Halal Science Graduates specifically in the education sector as it is well known that ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
0
0
Order By: Relevance
“…Asia Pacific houses the most Muslims, followed by the Middle East, Sub-Saharan Africa, Europe, North and finally Latin America (Aniqoh & Hanastiana, 2020). Deuraseh et al (2022) stated that the population of Muslims will always increase and is believed to dominate up to two-fifth of the world's population in the future. Due to the presence of the largest population of Muslims, Asia Pacific is the largest market available for the growth of Halal foods and beverages from the aspect of revenue (Handani, 2021).…”
Section: 1mentioning
confidence: 99%
“…Asia Pacific houses the most Muslims, followed by the Middle East, Sub-Saharan Africa, Europe, North and finally Latin America (Aniqoh & Hanastiana, 2020). Deuraseh et al (2022) stated that the population of Muslims will always increase and is believed to dominate up to two-fifth of the world's population in the future. Due to the presence of the largest population of Muslims, Asia Pacific is the largest market available for the growth of Halal foods and beverages from the aspect of revenue (Handani, 2021).…”
Section: 1mentioning
confidence: 99%
“…In recent years, the innovations in HT products and services have been fueled by science and technology to meet the emerging needs of the people. Academic and training programs are developed to educate and nurture the so-called halal talents i.e., the human capital to meet the demand of the halal industry (Rafida et al, 2013;Deuraseh et al, 2022). More recently, in Malaysia, two main bodies of knowledge for halal-related academic programs or studies have been identified to assist in this capacity building, i) management, and ii) applied science (Malaysia Qualifications Agency, 2022).…”
Section: Introductionmentioning
confidence: 99%